Penerapan Prinsip Syirkah Abdan dalam Pembagian Harta Perkawinan - Salsabila Firdausia; Zeehan Fuad Attamimi (Syntax Idea)
Law Number 1 of 1974 explains the division of Marital Property, stating that property acquired during marriage and inherited by each spouse is called joint property. The Compilation of Islamic Law contains regulations governing the division of joint property in the context of Islamic marriages. Syirkah Abdan, as a principle in the division of marital property, can serve as a basis for implementing a fair distribution principle in accordance with the contributions of each party. If both parties agree, the division of joint property can be based on customary law, religious law, or other legal frameworks. The application of the Syirkah Abdan principle in the division of marital property is expected to ensure justice and equality between husband and wife. In this context, the active role and real contributions of both parties are recognized in a balanced manner, in line with the principles of Syirkah itself. This research makes a significant contribution to designing policies and practical guidelines to ensure the active contributions of husbands and wives are acknowledged and fairly valued in the division of marital property. The aim of this research is to explore a deep understanding of the implementation of the Syirkah Abdan principle in the division of marital property and the conception of marital property according to the Compilation of Islamic Law and Law Number 1 of 1974. The application of the Syirkah Abdan principle in the division of marital property is the main focus to identify its processes and impacts in the context of marital relationships. The research methodology used is normative legal research with a literature research methodology; primary, secondary, and tertiary legal library sources were examined.